2023
DOI: 10.15587/1729-4061.2023.276251
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the production technology of tokay wines based on the revealed effect of enzyme activity on the quality of grape variety

Abstract: Wines of the Tokay type are produced using a special technology. According to Hungarian technology, for the production of these wines, bunches of white and red grape varieties are twisted on the vine, withered for a certain time, then dropped for processing. At the same time, the percentage of sugar in grapes is artificially increased due to the evaporation of moisture. In pre-dried grapes, the percentage of sugar should be in the range of 40–45 %. For the production of Tokay-type wines, the fermentation of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Data in Tables 7,8 showed that the smallest amount of the main quality indicators of persimmon fruits was little spent on the breathing process in the fifth variant. In addition, individual representatives of phenolic compounds in persimmon varieties were studied by a modern method of analysis for different variants.…”
Section: Fig 3 Quantitative Change In Pectin Substances During Storag...mentioning
confidence: 99%
See 2 more Smart Citations
“…Data in Tables 7,8 showed that the smallest amount of the main quality indicators of persimmon fruits was little spent on the breathing process in the fifth variant. In addition, individual representatives of phenolic compounds in persimmon varieties were studied by a modern method of analysis for different variants.…”
Section: Fig 3 Quantitative Change In Pectin Substances During Storag...mentioning
confidence: 99%
“…In [8], the dynamics of changes in the activity of ascorbate oxidase, o-diphenol oxidase, peroxidase, and catalase enzymes belonging to the class of oxidoreductases in plant raw materials were studied. It is known that in all living organisms the metabolic process proceeds with the participation of enzymes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in enzyme activity creates conditions for the consumption of its constituent nutrients for the respiration process. This means that, compared to withered grapes, the amount of nutrients in ripened grapes is significantly higher [6].…”
Section: Introductionmentioning
confidence: 98%